Berseem-Rhizobium symbiosis boosted growth and yield in the presence of rhizobacteria - Qureshi, Muhammad Amjad; Niaz, Abid; Ali, M. Asif; Ehsan, Shabana; Ehsan, Shabana; Javed, Hina; Rafique, Munazza; Ijaz, Fraza; Shehzad, Armghan; Nawaz, Allah (Journal of Pure and Applied Agriculture, 2023)
Legume-Rhizobium symbiotic relationships produced is beneficial and provides a natural mode of N2-fixation via the mini nitrogen factories i.e., nodules. The species of Rhizobium has an extraordinary ability to fix nitrogen to plants species and resultantly less mineral nitrogen is required for crop growth. Filed study was designed on berseem to assess the symbiotic and rhizobacteria on berseem growth and yield under varied levels of nitrogen. The screening of isolates of symbionts and non-symbionts (04 of each) has been carried out for different biochemical functions. The bacterial isolates showed promising results for IAA equivalents, solubilization index, siderophore unit (quantitively & qualitatively) and other tests were done in field experiment at varied nitrogen levels i.e., 15 & 30 kg N ha-1. Results revealed that bacterial inoculation either applied separately or in combined form demonstrated significant results at each N level in comparison to control. Results of yield contributing components suggested that co-inoculation produced higher berseem fodder & dry matter yield i.e., 76.7, 16.3 t ha-1 at 30 kg N ha-1 in comparison to 76.2, 15.7 t ha-1 at 15 kg N ha-1, respectively. Co-inoculation also improved the nodule no. and nodular mass i.e., 28.5 and 0.254 g plant-1 as compared to the remaining inoculation levels at higher level of N. Co-inoculation (Br4 & Pg4) produced the maximum seed yield i.e., 368.7 kg ha-1 than control i.e., 331.7 kg ha-1. Higher N-P content was observed in seed and plant matter in different cuttings of berseem due to co-inoculation. The synergism between Rhizobium sp and rhizobacteria could be used after thorough screening and more valued approach as compared to separate application of microbes. Studies should be carried out to various legumes to accomplish beneficial effects of rhizobacteria along with symbionts to improve yield contributing factors and other quality indicators.